The Decolonial Thought: Challenges and Contributions to Education - Velazquez Tello, Maria (My University, 2018)
The decolonial thought is an emergent Latin American movement that proposes a critical analysis to understand current dominant paradigms in Latin America in relation to colonization from Europe. The aim of this thesis is to find out what the contributions and challenges of the decolonial thought are in the context of education in Latin America. This study was conducted through a Systematized Literature Review, which included 70 academic papers from literary search from year 1980 to 2018 that is the period the decolonial theme emerged. In addition, the text Sí a la Vida (Martínez, 2018), which is a narrative of a decolonial pedagogue in Mexico, was also a central text analysed in this thesis. Content analysis was used to analyse the data. In terms of contributions, the decolonial perspective offers elements for study and reflection on teaching and learning processes from the voices of Latin Americans, which brings ancestral knowledge into focus. On the other hand, considering that schools are often obliged to respond to globalization demands, taking the decolonial perspective into practice seems to be one of the major challenges as it implies swimming against the tide. In this regard, literature showed that some teachers and theorists find themselves in contradictory positions as decolonial scholars immersed in the institutions and policies they often critique. Hence, another challenge of adopting the decolonial thought is to embrace a critical perspective of decoloniality that includes reconciliation rather than only decolonizing; which can be the focus of further studies of the decolonial thought.
Keywords: Decolonial thought, Decolonial Pedagogy, challenges and contributions to education, Latin America.